Analisis Wacana Sakubun Sub-tema Kegemaran - Putri Pemayun, A.A Pradnyani; Hermawan, Gede Satya; Yeni, Yeni (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025)DO - 10.24843/PJIIB.2025.v25.i01.p15, 2025)
Students XI IBB1 at SMAN 1 Sukasada can describe themselves well through essays. Grammatical errors and inaccurate use of particles were found in students' Japanese essays, but this did not detract from the information they wanted to convey. Some students write that focus on on-point information without continuing the beginning information. There are also essays whose coherence is weak. Two pieces of information are provided without containing further information. This deficiency is caused by the students being beginner Japanese language learners. The Japanese language beginner-level students' knowledge and skills in Japanese are still limited. The vocabulary and grammar used are limited to the material studied. The expressions and choice of words used also had barriers.